UMP, MNR and UMW collaboration in food grade grease oil research - Laili, Zulkepeli (UMPSA, 2022)
KUALA LUMPUR, 22 March 2022 – Universiti Malaysia Pahang (UMP) will partner with Multitech Sdn. Bhd. (MNR) and UMW Innovation and R&D Centre Sdn. Bhd. in carrying out food grade grease oil research project.